Dexmedetomidine and Netrin-1 Combination Therapy Inhibits Endoplasmic Reticulum Stress by Regulating the ERK5/MEF2A Pathway to Attenuate Cerebral Ischemia Injury - Yin, Jiang-Wen; Li, Jia; Ren, Yi-Min; Li, Yan; Wang, Rui-Xue; Wang, Sheng; Zuo, Yun-Xia (Frontiers in Neuroscience, 2021)
The complexity of hard-to-treat diseases such as ischemic stroke strongly undermines the therapeutic potential of available treatment options. Therefore, current developments have gently shifted from a focus on monotherapy to combined or multiple therapies. Both dexmedetomidine and netrin-1 have anti-neuronal apoptosis effects, but the mechanism is still unclear. The study aimed to estimate the efficacy of dexmedetomidine and Netrin-1 combination therapy against ERS-induced apoptosis after cerebral ischemia injury in vivo and in vitro, and whether the mechanism is related to the ERK5/MEF2A pathway. Adult male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) in vivo, 90 min ischemia and 24 h reperfusion. The hippocampus slices used to establish oxygen-glucose deprivation (OGD) injury model in vitro. Neterin-1 and Dexmedetomidine were pretreated and post-treated respectively before and after the model establishment. MEF2A knockdown was performed by microinjection of AAV9-MEF2A RNAi vector. Orthodromic population spike (OPS) at the end of reoxygenation were recorded. Neurobehavioral tests, TTC staining, Nissl staining, TUNEL staining were performed to assess the effect of the drugs. The expression of CHOP, GRP78, MEF2A, ERK5, p-ERK5 were investigated by Western blot and immunofluorescence staining. Neurological deficit score, infarct volume, the expression of GRP78, CHOP, and neural apoptotic rate of MCAO group increased markedly. Combination of dexmedetomidine and Netrin-1 resulted in lower infarct volumes and fewer neurological impairments, higher OPS recovery rate, and less damaged and apoptotic cells after cerebral ischemia injury. Furthermore, expression levels of GRP78 and CHOP decreased in the combination therapy group, and it was more effective than the single drug group. Meanwhile, Combination of dexmedetomidine and Netrin-1 increased MEF2A expression and promoted ERK5 phosphorylation. However, the protective effect of dexmedetomidine combined with Netrin-1 in improving neurological function was significantly eliminated by pre-knockdown MEF2A. The neuroprotective effects of dexmedetomidine combined with Netrin on cerebral ischemia-reperfusion injury and hippocampal hypoxia injury in terms of ERS. The synergistic effect of combination therapy is related to the activation of ERK5/MEF2A signaling pathway.